High toughness composite material for foldable stowable cases and method of making same

CN122356659BActive Publication Date: 2026-10-27HUBEI YOUNA TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610831805.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-10-27
Estimated Expiration
2046-06-10

AI Technical Summary

Technical Problem

但是,大量添加橡胶或增塑剂虽然可以显著提高韧性,却会导致材料刚性和硬度明显下降

Benefits of technology

1.本发明通过HTPB@SiO2-壳聚糖微胶囊的设计,使得HTPB橡胶在基体熔融共混时不直接释放出来,不会严重降低材料模量和硬度;另一方面,通过壳聚糖外壳,提高微胶囊在熔融挤出过程中的稳定性和分散性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122356659B_ABST
    Figure CN122356659B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of polymer material modification, and particularly relates to a high-toughness composite material for a foldable storage box and a preparation method thereof; in view of the problem that in the prior art, a large amount of elastomer or plasticizer is added to improve the toughness of a polypropylene foldable storage box, resulting in a significant decrease in modulus of the material and easy deformation of the box body; the application takes hydroxyl-terminated polybutadiene as a core material and tetraethyl orthosilicate as a silicon source, forms a SiO2 shell layer through a sol-gel method at an O / W emulsion interface, and then forms microcapsules through spray drying in a chitosan solution; then the microcapsules are mixed with a base resin, a compatibilizer and the like to be granulated and injection molded; finally, the whole or local alkali treatment is performed to activate the microcapsules at folds or corners to break and release the hydroxyl-terminated polybutadiene, so that local toughening is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer material modification technology, specifically relating to a high-toughness composite material for foldable storage boxes and its preparation method. Background Technology

[0002] Foldable storage boxes are typically made of polypropylene (PP), taking advantage of PP's lightweight, high strength, corrosion resistance, and ease of processing (CN121362406A). However, PP is a semi-crystalline thermoplastic polymer, and isotactic PP has high crystallinity, resulting in poor toughness at low temperatures or under impact, making it prone to stress cracking at repeatedly folded areas. To improve the impact toughness and cold resistance of PP materials, a common method is to blend elastomers or plasticizers into the PP matrix. However, while adding large amounts of rubber or plasticizers can significantly improve toughness, it leads to a significant decrease in material rigidity and hardness. Furthermore, when adding plasticizers to improve low-temperature resistance, problems such as plasticizer migration and material softening and stickiness can occur.

[0003] Several technical approaches have been proposed to improve the mechanical and heat resistance properties of polymer films. For example, introducing nanofillers can improve the rigidity of PP to a certain extent and induce the formation of fine grains, thereby improving impact resistance. Another example is the use of microencapsulated toughening agents, which can release the toughening agent when microcracks form due to impact, thus passivating or healing the cracks and improving toughness and extending lifespan.

[0004] In summary, the present invention aims to provide a new toughening modification scheme that improves the folding resistance of PP material without sacrificing its original strength and hardness by using microencapsulated toughening agents. Summary of the Invention

[0005] This invention provides a high-toughness composite material for foldable storage boxes and its preparation method. When used in foldable storage boxes, it can significantly improve toughness while maintaining high material rigidity, thus preventing the box from deforming due to excessive softness during use.

[0006] The specific technical solution is as follows: A high-toughness composite material for foldable storage boxes and its preparation method are as follows: S1: Preparation of monolayer microcapsules.

[0007] S11: Hydroxyl-terminated polybutadiene is mixed with tetraethyl orthosilicate, and then sorbitan fatty acid ester is added. The mixture is heated and stirred to obtain an oil phase solution.

[0008] S12: Add Tween-80 to deionized water and stir to obtain an aqueous solution.

[0009] S13: The oil phase solution prepared in S11 is added to the aqueous phase solution prepared in S12, shear emulsified, pH adjusted to 9-11, stirred, and tetraethyl orthosilicate hydrolyzed and condensed at the water-contactable oil droplet interface. After cooling, centrifugation, washing, and drying, HTPB@SiO2 monolayer microcapsules containing hydroxyl-terminated polybutadiene core material and SiO2 shell enrichment layer are obtained.

[0010] S2: Microcapsule preparation.

[0011] S21: Add glacial acetic acid to deionized water, stir, then add chitosan powder, continue stirring, let stand to remove bubbles, and obtain chitosan acetic acid aqueous solution.

[0012] S22: The HTPB@SiO2 monolayer microcapsules prepared in S13 are added to the chitosan acetate aqueous solution prepared in S21, dispersed, and spray-dried to obtain HTPB@SiO2-chitosan microcapsules.

[0013] S3: Mixing and processing: Homopolymer polypropylene, HTPB@SiO2-chitosan microcapsules prepared in S2, auxiliary toughening agent, and polypropylene grafted maleic anhydride are dried and mixed. Then, antioxidant 1010 is added, stirred, melt-extruded, cooled and shaped, granulated, and dried to obtain a high-toughness composite material.

[0014] Furthermore, the hydroxyl-terminated polybutadiene described in S11 has a mass ratio of 2:1 to 4:1 with tetraethyl orthosilicate.

[0015] The amount of the dehydrated sorbitan fatty acid ester described in S11 is 2% to 5% of the total mass of the terminal hydroxyl polybutadiene and tetraethyl orthosilicate.

[0016] The heating and stirring described in S11 has the following parameters: temperature 38-42℃, rotation speed 100-300rpm, and duration 30-60min.

[0017] Furthermore, the amount of Tween-80 mentioned in S12 is 1% to 3% of the total mass of the aqueous phase.

[0018] Furthermore, the oil phase solution described in S13 has an oil-to-water ratio of 1:3 with the aqueous phase solution.

[0019] The shear emulsification described in S13 has the following parameters: 5000-10000 rpm, duration 10-20 min.

[0020] The stirring described in S13 has the following parameters: temperature 35-45℃, speed 200-400rpm, and duration 4-8h.

[0021] The centrifugal separation described in S13 has the following parameter settings: rotation speed 8000~10000rpm, duration 10~15min.

[0022] Furthermore, in the chitosan acetic acid aqueous solution described in S21, the volume fraction of glacial acetic acid is 1% to 2%, and the mass concentration of chitosan is 1 wt% to 3 wt%.

[0023] The HTPB@SiO2 monolayer microcapsules described in S22 have a mass ratio of 5:1 to 10:1 with chitosan in the chitosan acetate aqueous solution.

[0024] The dispersion process described in S22 has the following parameter settings: rotation speed 5000-8000 rpm, duration 5-10 min.

[0025] The spray drying described in S22 has the following parameter settings: inlet air temperature 140~160℃, outlet air temperature 70~90℃, and rotation speed 20000~30000rpm.

[0026] Furthermore, the melt extrusion described in S3 has the following parameter settings: feeding zone temperature 180-190℃, melting zone temperature 190-200℃, mixing zone temperature 200-210℃, homogenization zone temperature 200-210℃, die head temperature 210-220℃, and screw speed 300rpm.

[0027] The high-toughness composite material described in S3 has the following composition of raw materials: 60-80 parts of homopolymer polypropylene, 10-20 parts of auxiliary toughening agent, 5-15 parts of HTPB@SiO2-chitosan microcapsules, 3-8 parts of polypropylene grafted with maleic anhydride, and 0.1-0.5 parts of antioxidant 1010.

[0028] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention, through the design of HTPB@SiO2-chitosan microcapsules, ensures that HTPB rubber is not directly released during the melt blending of the matrix, thus avoiding a significant reduction in the material's modulus and hardness. On the other hand, the chitosan shell enhances the stability and dispersibility of the microcapsules during melt extrusion.

[0029] 2. The present invention improves the toughness of the product by subsequently impregnating or spraying with alkaline solution to partially dissolve or rupture the outer shell of the microcapsule. Attached Figure Description

[0030] Figure 1 This is a process flow diagram for the preparation of a high-toughness composite material used in foldable storage boxes.

[0031] Figure 2 These are FTIR images of hydroxyl-terminated polybutadiene, HTPB@SiO2 monolayer microcapsules, and HTPB@SiO2-chitosan microcapsules from Example 1.

[0032] Figure 3These are SEM images of the foldable storage box and the pure polypropylene matrix in Example 1, wherein... Figure 3 A is a SEM image of the fracture surface of a pure polypropylene matrix. Figure 3 B is a SEM image of the fracture surface of the composite material after alkali activation. Figure 3 C is a SEM image of the microcapsules immediately upon contact with the alkaline solution. Figure 3 D is Figure 3 SEM image of the ruptured spherical shell in section B.

[0033] Figure 4 These are TEM images of the HTPB@SiO2 monolayer microcapsules and HTPB@SiO2-chitosan microcapsules from Example 1. Figure 4 A is a TEM image of HTPB@SiO2 monolayer microcapsules. Figure 4 B is a TEM image of HTPB@SiO2-chitosan microcapsules. Figure 4 C is Figure 4 Enlarged view of HTPB@SiO2-chitosan microcapsules in section B.

[0034] Figure 5 This is a DLS diagram of the HTPB@SiO2-chitosan microcapsules in Example 1.

[0035] Figure 6 The diagram shows the zeta potentials of the HTPB@SiO2 monolayer microcapsules, HTPB@SiO2-chitosan microcapsules, and HTPB@SiO2-chitosan microcapsules treated with alkali solution in Example 1. Detailed Implementation

[0036] The following embodiments further explain and illustrate the technical solutions of the present invention. It should be specifically noted that each specific embodiment is a concretization and explanation of the technical solution and should not be considered as a limitation on the scope of protection of the present invention. Those skilled in the art still have the right to modify the technical solutions of these embodiments and make equivalent substitutions for some or all of the technical features, and these modifications or substitutions do not change the essence of the corresponding technical solutions, nor do they cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions described in the present invention.

[0037] This invention proposes a high-toughness composite material for foldable storage boxes and its preparation method. By designing a microcapsule with a core-shell-shell structure, the liquid toughening agent is temporarily "locked" within a rigid shell, ensuring it does not affect the rigidity of the matrix during injection molding. Before use, activation with an alkaline solution causes the microcapsules at the creases to selectively rupture, releasing HTPB to achieve localized in-situ toughening. (See attached diagram) Figure 1 The image shows a high-toughness composite material for foldable storage boxes and its preparation method. The detailed technical solution is as follows: 1. Preparation of monolayer microcapsules Hydroxyl-terminated polybutadiene (HTPB) was mixed with tetraethyl orthosilicate (TEOS), and then sorbitan fatty acid ester was added. The mixture was heated and stirred to obtain an oil phase solution. Tween-80 was added to deionized water and stirred to obtain an aqueous phase solution. The oil phase solution was added to the aqueous phase solution, sheared and emulsified, the pH was adjusted, stirred, cooled, centrifuged, washed, and dried to obtain HTPB@SiO2 monolayer microcapsules.

[0038] Through high-speed shearing and the stabilizing effect of emulsifiers, HTPB is dispersed into micron-sized oil droplets, uniformly suspended in the aqueous phase, forming an O / W emulsion. In this application, the oil droplets formed by HTPB and TEOS do not require all TEOS to migrate to the oil-water interface. After shear emulsification, the OH groups in the aqueous phase... - TEOS can preferentially contact the surface of the oil droplet and its near-interface region, causing it to undergo hydrolysis and condensation in the water-accessible area, forming a SiO2 shell-like enriched layer mainly composed of a Si-O-Si network. Since there may be a small amount of unmigrated TEOS or local SiO2 network inside the HTPB oil droplet, the HTPB@SiO2 monolayer microcapsule referred to in this application refers to a particle system with an HTPB embedded core material and a SiO2 shell-like enriched layer, rather than requiring all SiO2 to be strictly located at a single ideal interface.

[0039] 2. Microcapsule preparation Glacial acetic acid was added to deionized water and stirred. Then chitosan powder was added and stirred again. The mixture was allowed to stand to remove bubbles, resulting in a chitosan acetic acid aqueous solution. HTPB@SiO2 monolayer microcapsules were added to the chitosan acetic acid aqueous solution, dispersed, and spray-dried to obtain HTPB@SiO2-chitosan microcapsules.

[0040] In an aqueous acetic acid solution, the amino groups on the chitosan molecular chain are protonated to form -NH3. + The process disrupts intermolecular hydrogen bonds, causing chitosan to dissolve and form a positively charged polyelectrolyte solution. HTPB@SiO2 monolayer microcapsules act as the "core" and are uniformly dispersed in the chitosan solution. During spray drying, the suspension is dispersed into fine droplets by an atomizer, and the water on the droplet surface evaporates rapidly. As water is removed, the concentration of dissolved chitosan increases sharply, leading to gelation or deposition, forming a continuous, dense chitosan film on the microcapsule surface, encapsulating the HTPB@SiO2 microcapsules. Due to the extremely rapid drying speed, the chitosan molecules do not have time to rearrange and crystallize, resulting in a uniform coating layer with good redispersibility. In subsequent use, when exposed to alkaline solutions, the protonated amino groups on the chitosan molecular chains deprotonate, and the intermolecular hydrogen bonds are broken, causing the chitosan layer to swell, dissolve, or rupture, thus exposing the internal HTPB@SiO2 microcapsules. The exposed SiO2 shell is unstable in alkaline solutions, and OH... -Ions attack the Si-O-Si bonds in the SiO2 network, causing a nucleophilic substitution reaction that erodes and breaks the SiO2 shell under alkaline conditions, ultimately releasing the HTPB elastomer. Simultaneously, the chitosan outer layer acts as a protective layer, preventing premature breakage of the HTPB@SiO2 microcapsules due to shear forces during injection molding, ensuring stability before activation.

[0041] 3. Mixing and processing Homopolymer polypropylene, HTPB@SiO2-chitosan microcapsules, auxiliary toughening agent (polyolefin elastomer, POE), and polypropylene grafted maleic anhydride (PP-g-MAH) were dried and mixed separately. Then, antioxidant 1010 was added, stirred, melt-extruded, cooled and shaped, granulated, and dried to obtain a high-toughness composite material.

[0042] The material is subjected to strong shear force in the barrel, which makes the components fully mixed. POE, as an elastomer phase, is dispersed in the continuous PP phase to form a "sea-island" structure. The microcapsule powder is uniformly dispersed in the matrix under the action of shear and melt flow. The maleic anhydride groups on the PP-g-MAH molecular chain interact with the amino and hydroxyl groups on the chitosan layer of the microcapsule, which reduces the interfacial tension, improves the interfacial bonding force, and prevents the microcapsule agglomeration.

[0043] 4. Injection molding The high-toughness composite material is dried, then injection molded using an injection molding machine, and finally soaked in a hot water bath to remove stress, resulting in a storage box.

[0044] Inside the injection molding machine barrel, the masterbatch melts under heat and transforms into a homogeneous melt under the rotation and shearing action of the screw. Driven by injection pressure, it rapidly fills the mold cavity. The chitosan outer layer is not used as an inert shell that remains unchanged during high-temperature melting. This application controls the residence time and shear strength of microcapsules in the high-temperature melt, combined with antioxidant protection, to ensure that the microcapsules retain their delayed-release function after processing. Whether the microcapsules retain their function after processing is not only determined by the theoretical decomposition temperature, but also verified through the morphology of the microcapsules before and after extrusion, SEM / TEM of the composite material cross-section, Si element distribution, HTPB extraction leakage rate, TGA / DTG, and the detection of black spots / bubbles on the product appearance. As long as spherical microcapsules or spherical empty shell structures that can be triggered by creases and alkali solutions still exist after processing, the local toughening purpose of this application can be achieved. After filling the mold, the melt cools in the mold. The PP molecular chains begin to crystallize, forming a certain aggregated structure. Simultaneously, the distribution state of the microcapsules and POE dispersed phase in the PP matrix is ​​"frozen," forming the final microstructure of the product.

[0045] In this application, SiO2 is not added to the polypropylene matrix as a continuous inorganic filler skeleton, but rather exists as a thin-layered shell-like enriched structure within micron-sized microcapsules. Its dosage is limited by the amount of microcapsules added and the shell thickness, and it does not form a continuous rigid network within the matrix. After pre-folding and local activation with alkali solution at the crease sites, the SiO2 shell-like enriched layer undergoes localized cracking or erosion, releasing the HTPB core material. The cracked shell and the HTPB core material together induce crack deflection, passivation, and localized plastic deformation. Therefore, the role of the SiO2 shell is not to increase overall brittleness, but rather to achieve delayed release during processing and triggered release during use.

[0046] 5. Activate The box material is pre-folded, and then an alkaline solution is evenly sprayed or brushed onto the creases, corners, hinges and other key areas requiring high toughness, ensuring that these areas are fully wetted. The box is then left to stand, cleaned and dried (at 60°C for 2 hours) to obtain a foldable storage box.

[0047] During the pre-folding process, the polypropylene substrate at the fold of the housing experiences stress whitening and initial micro- and nano-scale microcracks due to intense local bending stress. These crack pathways, created by mechanical stress tearing the substrate, directly penetrate and crush the rigid shell in this stress-concentrated area. When a specific weakly alkaline solution is applied at this point, the alkali is no longer repelled by the substrate but instead rapidly penetrates into the deeper substrate through the opened capillary microcrack channels, aided by capillary force. The penetrating alkali promotes microscopic hydrolytic etching of the silica fracture surface under high stress, accelerating the structural disintegration of the rigid shell. Furthermore, the chitosan outer layer undergoes molecular chain deprotonation and rapid shrinkage upon contact with the alkali. This sudden contraction of the micro-volume further generates localized phase separation tensile stress, ultimately causing the multilayered constrained structure to completely collapse, releasing the low-viscosity liquid rubber encapsulated within, achieving in-situ passivation and plastic healing of the crack tips.

[0048] Example 1 A method for preparing a high-toughness composite material for a foldable storage box is as follows: Table 1 Main Raw Materials S1: Preparation of monolayer microcapsules.

[0049] S11: Hydroxyl-terminated polybutadiene and tetraethyl orthosilicate are mixed in a dry beaker, and then immediately sorbitan fatty acid ester is added. The mixture is heated and stirred to obtain an oil phase solution. The mass ratio of hydroxyl-terminated polybutadiene to tetraethyl orthosilicate is 3:1; the amount of sorbitan fatty acid ester added is 3.5% of the total mass of hydroxyl-terminated polybutadiene and tetraethyl orthosilicate; the heating and stirring parameters are set as follows: temperature 40℃, rotation speed 200 rpm, and time 45 min.

[0050] S12: Add Tween-80 to deionized water and stir to obtain an aqueous solution. The amount of Tween-80 added is 2% of the total mass of the aqueous phase.

[0051] S13: The oil phase solution prepared in S11 was added to the aqueous phase solution prepared in S12, shear emulsified, and the pH was adjusted to 10 by dropwise addition. The mixture was stirred, cooled, centrifuged, washed, and dried to obtain HTPB@SiO2 monolayer microcapsules. The DLS particle size, microstructure, and turbidity of the supernatant after centrifugation and washing were used as batch control indicators. The oil-to-water ratio between the oil and aqueous phase solutions was 1:3; the shear emulsification parameters were set to 7500 rpm for 15 min; the stirring parameters were set to 40℃, 300 rpm for 6 h; and the centrifugation parameters were set to 9000 rpm for 12.5 min.

[0052] S2: Microcapsule preparation.

[0053] S21: Add glacial acetic acid to deionized water, stir, then add chitosan powder, continue stirring, and allow to stand to remove bubbles to obtain a chitosan-acetic acid aqueous solution. The volume fraction of glacial acetic acid in the chitosan-acetic acid aqueous solution is 1.5%, and the mass concentration of chitosan is 2 wt%.

[0054] S22: The HTPB@SiO2 monolayer microcapsules prepared in S13 were added to the chitosan-acetic acid aqueous solution prepared in S21, dispersed, and spray-dried to obtain HTPB@SiO2-chitosan microcapsules. The mass ratio of HTPB@SiO2 monolayer microcapsules to chitosan in the chitosan-acetic acid aqueous solution was 7.5:1. The dispersion parameters were set as follows: 6500 rpm for 8 min; the spray drying parameters were set as follows: inlet air temperature 150℃, outlet air temperature 80℃, and 25000 rpm.

[0055] S3: Mixing and processing. Homopolymer polypropylene, HTPB@SiO2-chitosan microcapsules prepared in S2, auxiliary toughening agent, and polypropylene grafted maleic anhydride are dried and mixed separately. Then, antioxidant 1010 is added, stirred, melt-extruded, cooled and shaped, granulated, and dried to obtain a high-toughness composite material. The melt extrusion parameters are set as follows: feeding zone temperature 185℃, melting zone temperature 195℃, mixing zone temperature 205℃, homogenization zone temperature 205℃, die head temperature 215℃, and screw speed 300rpm. The composition of the high-toughness composite material is as follows: 70 parts homopolymer polypropylene, 15 parts auxiliary toughening agent, 10 parts HTPB@SiO2-chitosan microcapsules, 4.7 parts polypropylene grafted maleic anhydride, and 0.3 parts antioxidant 1010.

[0056] S4: Injection molding. The high-toughness composite material prepared in S3 is dried (90℃, 3 hours), then injection molded using an injection molding machine. It is then immersed in a hot water bath (70℃) and pre-folded. Next, sodium hydroxide solution is evenly sprayed or brushed onto key areas requiring high toughness, such as creases, corners, and hinge connections. The box is then left to stand, cleaned, and dried (60℃, 2 hours) to obtain a foldable storage box. Injection molding parameters are set as follows: feed section temperature 200℃, compression section temperature 215℃, metering section temperature 215℃, nozzle temperature 215℃, mold temperature 45℃, and injection pressure 100MPa.

[0057] Example 2 The composition and preparation process are the same as in Example 1, except that: In the preparation process, the mass ratio of hydroxyl-terminated polybutadiene to tetraethyl orthosilicate in S11 is 2:1; the amount of dehydrated sorbitan fatty acid ester added is 2% of the total mass of hydroxyl-terminated polybutadiene and tetraethyl orthosilicate, and other components are the same.

[0058] The heating and stirring parameters in step S11 of the preparation process are set as follows: temperature 38℃, rotation speed 100rpm, duration 30min, and other steps are the same.

[0059] In the preparation process, the amount of Tween-80 added to S12 is 1% of the total mass of the aqueous phase, and the other components are the same.

[0060] In the preparation process S13, the pH was adjusted to 9, the shear emulsification parameters were set to 5000 rpm for 10 min, the stirring parameters were set to 35℃, 200 rpm for 4 h, and the centrifugation parameters were set to 8000 rpm for 10 min. Other steps were the same.

[0061] In the preparation process S21, the volume fraction of glacial acetic acid in the chitosan acetic acid aqueous solution is 1%, the mass concentration of chitosan is 1 wt%, and other components are the same.

[0062] In the preparation process S22, the mass ratio of HTPB@SiO2 monolayer microcapsules to chitosan in chitosan acetate aqueous solution is 5:1, and other components are the same.

[0063] The dispersion parameters in step S22 of the preparation process are set as follows: rotation speed 5000 rpm, duration 5 min; the spray drying parameters are set as follows: inlet air temperature 140℃, outlet air temperature 70℃, rotation speed 20000 rpm, and other steps are the same.

[0064] The melt extrusion parameters in S3 of the preparation process are set as follows: feeding zone temperature 180℃, melting zone temperature 190℃, mixing zone temperature 200℃, homogenization zone temperature 200℃, die head temperature 210℃, and other steps are the same.

[0065] The composition of each raw material in S3 of the preparation process is as follows: 65 parts homopolymer polypropylene, 20 parts auxiliary toughening agent, 11.9 parts HTPB@SiO2-chitosan microcapsules, 3 parts polypropylene grafted maleic anhydride, 0.1 parts antioxidant 1010, and other components are the same.

[0066] In step S4 of the preparation process, potassium hydroxide solution is used, and the other components are the same.

[0067] Example 3 The composition and preparation process are the same as in Example 1, except that: In the preparation process, the mass ratio of hydroxyl-terminated polybutadiene to tetraethyl orthosilicate in S11 is 4:1; the amount of dehydrated sorbitan fatty acid ester added is 5% of the total mass of hydroxyl-terminated polybutadiene and tetraethyl orthosilicate, and other components are the same.

[0068] The temperature and stirring parameters in step S11 of the preparation process are set as follows: temperature 42℃, rotation speed 300rpm, duration 60min, and other steps are the same.

[0069] In the preparation process, the amount of Tween-80 added to S12 is 3% of the total mass of the aqueous phase, and the other components are the same.

[0070] In the preparation process S13, the pH was adjusted to 11, the shear emulsification parameters were set to 10,000 rpm for 20 min, the stirring parameters were set to 45℃, 400 rpm for 8 h, and the centrifugation parameters were set to 10,000 rpm for 15 min. Other steps were the same.

[0071] In the preparation process S21, the volume fraction of glacial acetic acid in the chitosan acetic acid aqueous solution is 2%, the mass concentration of chitosan is 3wt%, and other components are the same.

[0072] In the preparation process S22, the mass ratio of HTPB@SiO2 monolayer microcapsules to chitosan in chitosan acetate aqueous solution is 10:1, and other components are the same.

[0073] The dispersion parameters in step S22 of the preparation process are set as follows: rotation speed 8000 rpm, duration 10 min; the spray drying parameters are set as follows: inlet air temperature 160℃, outlet air temperature 90℃, rotation speed 30000 rpm, and other steps are the same.

[0074] The melt extrusion parameters in S3 of the preparation process are set as follows: feeding zone temperature 190℃, melting zone temperature 200℃, mixing zone temperature 210℃, homogenization zone temperature 210℃, die head temperature 220℃, and other steps are the same.

[0075] The composition of each raw material in S3 of the preparation process is as follows: 80 parts of homopolymer polypropylene, 10 parts of auxiliary toughening agent, 5 parts of HTPB@SiO2-chitosan microcapsules, 4.5 parts of polypropylene grafted maleic anhydride, 0.5 parts of antioxidant 1010, and other components are the same.

[0076] Sodium silicate solution is used in step S4 of the preparation process, while the other components are the same.

[0077] Example 4 The composition and preparation process are the same as in Example 1, except that: In the preparation process, the mass ratio of hydroxyl-terminated polybutadiene to tetraethyl orthosilicate in S11 is 3.5:1; the amount of dehydrated sorbitan fatty acid ester added is 4% of the total mass of hydroxyl-terminated polybutadiene and tetraethyl orthosilicate, and other components are the same.

[0078] The temperature and stirring parameters in step S11 of the preparation process are set as follows: temperature 39℃, rotation speed 250rpm, duration 40min, and other steps are the same.

[0079] In the preparation process, the amount of Tween-80 added to S12 is 2.5% of the total mass of the aqueous phase, and the other components are the same.

[0080] In the preparation process S13, the pH was adjusted to 9.5, the shear emulsification parameters were set to 6000 rpm for 18 min, the stirring parameters were set to 42℃, 360 rpm for 7 h, and the centrifugation parameters were set to 9500 rpm for 12 min. Other steps were the same.

[0081] In the preparation process S21, the volume fraction of glacial acetic acid in the chitosan acetic acid aqueous solution is 1.8%, the mass concentration of chitosan is 1.5 wt%, and other components are the same.

[0082] In the preparation process S22, the mass ratio of HTPB@SiO2 monolayer microcapsules to chitosan in chitosan acetate aqueous solution is 9:1, and other components are the same.

[0083] The dispersion parameters in step S22 of the preparation process are set as follows: rotation speed 7000 rpm, duration 9 min; the spray drying parameters are set as follows: inlet air temperature 155℃, outlet air temperature 85℃, rotation speed 28000 rpm, and other steps are the same.

[0084] The melt extrusion parameters in step S3 of the preparation process are set as follows: feeding zone temperature 188℃, melting zone temperature 194℃, mixing zone temperature 205℃, homogenization zone temperature 207℃, die head temperature 218℃, and other steps are the same.

[0085] The composition of each raw material in S3 of the preparation process is as follows: 60.8 parts of homopolymer polypropylene, 18 parts of auxiliary toughening agent, 15 parts of HTPB@SiO2-chitosan microcapsules, 6 parts of polypropylene grafted maleic anhydride, 0.2 parts of antioxidant 1010, and other components are the same.

[0086] Comparative Example 1 The composition and preparation process are the same as in Example 1, except that: In step S2 of the preparation process, the outer layer of chitosan is removed, and the HTPB@SiO2 monolayer microcapsules are directly mixed with the substrate for granulation. The other steps are the same.

[0087] Comparative Example 2 The material is toughened using conventional elastomers: 70 parts homopolymer polypropylene, 25 parts auxiliary toughening agent POE, 5 parts PP-g-MAH, and 0.3 parts antioxidant. No alkali activation treatment is performed.

[0088] Samples were taken from the hydroxyl-terminated polybutadiene and HTPB@SiO2 monolayer microcapsules in S1 and the HTPB@SiO2-chitosan microcapsules in S2, respectively. The hydroxyl-terminated polybutadiene was treated with potassium bromide salt film coating, and the HTPB@SiO2 monolayer microcapsules and HTPB@SiO2-chitosan microcapsules were treated with potassium bromide tableting. Fourier transform infrared spectroscopy (scanning range 4000–400 cm⁻¹) was used for testing. -1 (32 scans) Figure 2 As shown, for pure liquid hydroxyl-terminated polybutadiene, at 3400–3600 cm⁻¹ -1 A distinct and relatively broad absorption band appears, mainly due to the dispersion of OH stretching vibration energy caused by intermolecular hydrogen bonding between terminal hydroxyl groups, at 1640 cm⁻¹. -1 Nearby, there is an asymmetric stretching vibration of the carbon-carbon double bond, at 960 cm⁻¹. -1 Nearby, out-of-plane bending vibrations are observed in the inverse -1,4-structure double bond at 910 cm⁻¹. -1 Nearby, the characteristic bending vibration of the 1,2-vinyl double bond in the side chain is observed at 710 cm⁻¹. -1 Nearby, the characteristic bending vibrations of the cis-1,4- double bond are observed. For HTPB@SiO2 monolayer microcapsules, the spectrum of this layer retains the aforementioned characteristic peaks of HTPB, indicating that the core material has not undergone oxidative degradation, cross-linking hardening, or loss of activity, within the range of 1110–950 cm⁻¹. -1 A complex absorption band appears in the range of 1110–1000 cm⁻¹. -1 The asymmetric stretching vibrations of the Si-O-Si framework bonds in the three-dimensional silicon-oxygen network formed by the hydrolysis and condensation of tetraethyl orthosilicate lead to these vibrations in the range of 1000–950 cm⁻¹. -1The characteristic stretching vibration peaks of the Si-OH end groups remaining after incomplete polymerization indicate the successful formation of the rigid silica network at 750 cm⁻¹. -1 and 460cm -1 Near the 3200–3400 cm⁻¹, there are moderate characteristic peaks for the symmetric stretching vibrations and out-of-plane bending vibrations of the Si-O-Si bonds. For HTPB@SiO₂-chitosan microcapsules, these peaks are located at 3200–3400 cm⁻¹. -1 The spectral morphology changes; the bottom absorption band is covered and broadened by the OH stretching vibrations and NH stretching vibrations in the chitosan molecules, forming a broad absorption envelope at 1650 cm⁻¹. -1 Nearby, the carbonyl stretching vibration occurs at 1570 cm⁻¹. -1 Nearby, there are in-plane bending vibrations of primary amino groups and variable-angle vibrations of NH groups, at 1310 cm⁻¹. -1 Nearby, there is CN stretching vibration at 1020 cm. -1 Nearby, the CO stretching of primary alcohols and the CN stretching of primary amines in the chitosan backbone strongly coordinate, forming overlapping strong peaks.

[0089] Samples were taken from the foldable storage box prepared in S4 of Example 1. The shallow crease area of ​​the treated box was cut as an observation sample. Tensile tests were performed on pure polypropylene matrix (control group) and the composite material after alkali activation. The portion containing the fresh fracture surface was cut as a sample and then sputtered with gold. The samples were tested using a scanning electron microscope (accelerating voltage 7kV, working distance 8mm). Figure 3 As shown, where, Figure 3 Fracture A represents the untreated pure polypropylene matrix, exhibiting typical brittle fracture characteristics. The fracture surface is smooth, with a glass-like mirror finish, accompanied by straight and slender radial tear ridges. This indicates that the microcracks underwent a rapid, unimpeded propagation phase after initiation, and the material matrix failed to provide an effective energy dissipation pathway. Figure 3 B represents the fracture surface of the composite material after alkaline stimulation. The fractured spherical hollow shells embedded in the matrix indicate that physicochemical changes occurred within the material after infiltration treatment with a weakly alkaline chemical medium. Figure 3 C represents the changes in the microcapsules upon initial contact with the alkaline solution. The surface of the inorganic spherical inner shell begins to be covered with pores and grooves, eventually leading to the disintegration of the shell. Figure 3 D is Figure 3 The microstructure of the fractured spherical shell in B shows extensive serrated ridges and highly stretched polymer fibrils around the micropores, which dissipate impact energy and improve fracture toughness.

[0090] Samples of the HTPB@SiO2 monolayer microcapsules in S1 and the HTPB@SiO2-chitosan microcapsules in S2 of Example 1 were taken and placed in a 1:1 volume ratio of ethanol and water mixture. The mixture was ultrasonically dispersed, and 5 μL of the dispersion was pipetted onto a carbon film copper grid. After standing for 60 seconds, excess liquid was absorbed from the edges with filter paper, and the mixture was allowed to air dry for 12 hours. Observation was performed using a transmission electron microscope (TEM) (accelerating voltage 120 kV). Figure 4 As shown, where, Figure 4 A is a TEM image of HTPB@SiO2 monolayer microcapsules. Figure 4 B is a TEM image of HTPB@SiO2-chitosan microcapsules. Figure 4 C is Figure 4 Enlarged image of HTPB@SiO2-chitosan microcapsules in section B. Figure 4 In A, the HTPB@SiO2 monolayer microcapsules are spherical or nearly spherical with clear particle edges, indicating that TEOS undergoes hydrolysis and condensation at the O / W emulsion interface to form a continuous SiO2 shell. The average particle size of the monolayer microcapsules is about 2.65±0.50μm, and the SiO2 shell thickness is about 35±6nm. Figure 4 In B, the HTPB@SiO2-chitosan microcapsules still maintain a spherical or near-spherical morphology. Figure 4 A low-electron-density organic layer can be observed on the outer side of particles C, indicating that chitosan is deposited on the surface of HTPB@SiO2 monolayer microcapsules during spray drying, and the thickness of the outer chitosan layer is about 25±5nm. Compared with monolayer microcapsules, the edges of particles coated with chitosan change from relatively sharp to slightly blurred outer edge structure, indicating that the microcapsules have a multilayer structure, which can serve as a morphological basis for subsequent DLS particle size distribution and zeta potential changes.

[0091] Samples of the HTPB@SiO2-chitosan microcapsules in S2 of Example 1 were taken, added to deionized water, and prepared into a dispersion of 0.05 mg / mL. The dispersion was ultrasonically dispersed, allowed to stand, and analyzed using a dynamic light scattering particle size analyzer (DLS) (wavelength 633 nm, scattering angle 173°, dispersion medium: deionized water). Figure 5 As shown, the DLS particle size distribution exhibits a unimodal distribution, with the main peak concentrated in the 2–4 μm range. No obvious large particle aggregation peaks were observed, indicating that HTPB@SiO2-chitosan microcapsules have good redispersibility in the aqueous phase. 50 The value is 2.83 μm, indicating that the bulk particle size of the microcapsules is in the micrometer range. 90 The PDI was 5.21 μm, indicating that the vast majority of particles were smaller than 5.5 μm, and the PDI was 0.218, indicating that the particle size distribution was relatively concentrated.

[0092] Samples of the HTPB@SiO2 monolayer microcapsules in S1 and the HTPB@SiO2-chitosan microcapsules in S2 from Example 1 were taken and added to a 1 mmol / L KCl solution to prepare a 0.1 mg / mL dispersion. The dispersion was then sonicated, allowed to stand, and the pH was adjusted to 6.0 ± 0.1. Separately, samples of the HTPB@SiO2-chitosan microcapsules prepared in S2 were treated with NaOH alkali solution and washed until near neutral, then adjusted to the same test pH for Zeta potential testing (dispersion medium: 1 mmol / L KCl aqueous solution). Figure 6 As shown, the Zeta potential of the HTPB@SiO2 monolayer microcapsules is -32.6 mV, indicating that its surface is mainly composed of a SiO2 shell. SiO2 surfaces contain silanol groups, some of which ionize in the aqueous phase to form Si-O. - Therefore, the particles are negatively charged overall. After being coated with chitosan, the Zeta potential of HTPB@SiO2-chitosan microcapsules changes from negative to +27.8mV. This is because the amino groups on the chitosan molecular chain can be protonated in weakly acidic to near-neutral aqueous phases to form -NH3. + This process makes the outer surface of the microcapsules positively charged. After treatment with alkali, the zeta potential of the microcapsules changes to -18.4 mV. This change indicates that after alkali treatment, the -NH3+ in the outer layer of chitosan... + Deprotonation occurs, and the positive charge is significantly reduced. At the same time, the chitosan layer shrinks, cracks, or partially desorbs, exposing the internal SiO2 shell, and the surface negative charge becomes dominant again.

[0093] Based on Examples 1-4 and Comparative Examples 1-2, samples of the prepared high-toughness composite materials were taken for tensile strength testing: the material was prepared into dumbbell-shaped specimens using an injection molding machine, and the width and thickness of three points on the parallel part of the specimen were measured and the average value was taken. Then, a tensile test was performed using a universal testing machine (5 mm / min, original gauge length 50 mm), and the maximum force value when the specimen broke was recorded. Ten sets of tests were performed and the average value was taken.

[0094] Combining Examples 1-4 and Comparative Examples 1-2, samples of the prepared high-toughness composite materials were taken for notched impact strength testing: the material was prepared into a long strip (80mm × 10mm × 4mm) using an injection molding machine. A standard notch (notch depth 2mm, notch radius 0.25mm) was machined at the middle position along the length of the sample. The sample was accurately placed on a support, and a pendulum impact testing machine was used for testing. Five sets of tests were performed, and the average value was taken. The calculation formula is as follows: , where a cN E represents the notched impact strength. c Here is the corrected absorbed energy, h is the sample height, and b is the sample height. N This represents the remaining width at the bottom of the notch in the sample.

[0095] Based on Examples 1-4 and Comparative Examples 1-2, samples of the prepared high-toughness composite materials were taken for flexural modulus testing: the material was prepared into a long strip (80mm×10mm×4mm) using an injection molding machine, and the sample was placed symmetrically on two supports (the distance between the supports was 16 times the thickness of the sample), ensuring that its length direction was perpendicular to the axis of the supports. The test was performed using a universal testing machine (2mm / min), and its slope was calculated. Five sets of tests were performed, and the average value was taken.

[0096] Based on Examples 1-4 and Comparative Examples 1-2, samples of the finally prepared foldable storage boxes were taken for stacking deformation tests: the samples were placed in an environment of 23°C and 50% relative humidity for 24 hours, and then placed on the lower platen of the stacking test machine. Pressure was applied uniformly at a speed of 10 mm / min until the predetermined load was reached and maintained for 24 hours. The displacement of the center of the side of the box was measured. Five sets of tests were conducted, and the average value was taken.

[0097] The specific test results are shown in Table 2. Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 As shown: Table 2 Comparison of core performance of Examples 1-4 and Comparative Examples 1-2 The comparison results above show that Example 1 has the best overall performance. The preparation of microcapsules and subsequent activation with alkali solution achieves minimal stacking deformation while maintaining high toughness. This indicates that Example 1 successfully solves the problem of significantly improving toughness while maintaining high material rigidity, thus avoiding deformation of the box due to excessive softness during use. Examples 2 to 4 have slightly lower overall performance than Example 1 but still maintain a high level, indicating that excellent performance balance was achieved even with a wide range of parameter variations. In Comparative Example 1, the outer chitosan layer was removed, and HTPB@SiO2 monolayer microcapsules were directly mixed with the substrate for granulation, resulting in a decrease in both impact strength and modulus. In Comparative Example 2, conventional elastomers were used for toughening, resulting in high impact strength but significantly reduced modulus and hardness, and severe stacking deformation.

[0098] In summary, it is clear from the above embodiments and comparative examples that the high-toughness composite material provided by the present invention is significantly superior to traditional solutions in terms of tensile strength, flexural modulus, and stacking deformation. This is attributed to the construction of microcapsules and alkali activation, thereby achieving the solution of toughening problem while maintaining high modulus.

Claims

1. A high-toughness composite material for foldable storage boxes, characterized in that: By weight, the high-toughness composite material comprises 60-80 parts homopolymer polypropylene, 10-20 parts auxiliary toughening agent, 5-15 parts HTPB@SiO2-chitosan microcapsules, 3-8 parts polypropylene grafted maleic anhydride, and 0.1-0.5 parts antioxidant 1010; the auxiliary toughening agent is ethylene-octene copolymer; the HTPB@SiO2-chitosan microcapsules consist of an HTPB core layer, a SiO2 intermediate layer, and a chitosan outer layer from the inside out; the preparation method of the HTPB@SiO2-chitosan microcapsules is as follows: S1: Preparation of monolayer microcapsules; S11: Hydroxyl-terminated polybutadiene is mixed with tetraethyl orthosilicate, and then sorbitan fatty acid ester is added. The mixture is heated and stirred to obtain an oil phase solution. S12: Add Tween-80 to deionized water and stir to obtain an aqueous solution; S13: Add the oil phase solution prepared in S11 to the aqueous phase solution prepared in S12, shear emulsify, adjust the pH to 9-11, stir, and allow tetraethyl orthosilicate to hydrolyze and condense at the water-accessible oil droplet interface. Cool, centrifuge, wash, and dry to obtain HTPB@SiO2 monolayer microcapsules containing hydroxyl-terminated polybutadiene core material and SiO2 shell enrichment layer. S2: Microcapsule preparation; S21: Add glacial acetic acid to deionized water, stir, then add chitosan powder, continue stirring, let stand to remove bubbles, and obtain chitosan acetic acid aqueous solution; S22: The HTPB@SiO2 monolayer microcapsules prepared in S13 are added to the chitosan acetate aqueous solution prepared in S21, dispersed, and spray-dried to obtain HTPB@SiO2-chitosan microcapsules.

2. The high-toughness composite material for a foldable storage box according to claim 1, characterized in that: The polypropylene grafted with maleic anhydride has a grafting rate of 0.6% to 1.2%.

3. The high-toughness composite material for a foldable storage box according to claim 1, characterized in that: When the high-toughness polypropylene composite material is used in a foldable storage box, the box body is first pre-folded at the creases, corners, or hinge connections. Then, the above-mentioned areas are locally sprayed, brushed, or impregnated with alkaline solution, followed by cleaning and drying. The alkaline solution treatment is used to cause local rupture or shell erosion of the HTPB@SiO2-chitosan microcapsules in the stress concentration area, thereby releasing hydroxyl-terminated polybutadiene and passivating the crack tips.

4. A method for preparing a high-toughness composite material for a foldable storage box according to any one of claims 1-3, characterized in that, Includes the following steps: S1: Preparation of monolayer microcapsules; S11: Hydroxyl-terminated polybutadiene is mixed with tetraethyl orthosilicate, and then sorbitan fatty acid ester is added. The mixture is heated and stirred to obtain an oil phase solution. S12: Add Tween-80 to deionized water and stir to obtain an aqueous solution; S13: Add the oil phase solution prepared in S11 to the aqueous phase solution prepared in S12, shear emulsify, adjust the pH to 9-11, stir, and allow tetraethyl orthosilicate to hydrolyze and condense at the water-accessible oil droplet interface. Cool, centrifuge, wash, and dry to obtain HTPB@SiO2 monolayer microcapsules containing hydroxyl-terminated polybutadiene core material and SiO2 shell enrichment layer. S2: Microcapsule preparation; S21: Add glacial acetic acid to deionized water, stir, then add chitosan powder, continue stirring, let stand to remove bubbles, and obtain chitosan acetic acid aqueous solution; S22: The HTPB@SiO2 monolayer microcapsules prepared in S13 were added to the chitosan acetate aqueous solution prepared in S21, dispersed, and spray-dried to obtain HTPB@SiO2-chitosan microcapsules. S3: Mixing and processing: Homopolymer polypropylene, HTPB@SiO2-chitosan microcapsules prepared in S2, auxiliary toughening agent, and polypropylene grafted maleic anhydride are dried and mixed. Then, antioxidant 1010 is added, stirred, melt-extruded, cooled and shaped, granulated, and dried to obtain a high-toughness composite material.

5. The method for preparing a high-toughness composite material for a foldable storage box according to claim 4, characterized in that: The hydroxyl-terminated polybutadiene described in S11 has a mass ratio of 2:1 to 4:1 with tetraethyl orthosilicate. The amount of the dehydrated sorbitan fatty acid ester described in S11 is 2% to 5% of the total mass of hydroxyl-terminated polybutadiene and tetraethyl orthosilicate. The heating and stirring described in S11 has the following parameters: temperature 38-42℃, rotation speed 100-300rpm, and duration 30-60min.

6. The method for preparing a high-toughness composite material for a foldable storage box according to claim 4, characterized in that: The amount of Tween-80 mentioned in S12 added is 1% to 3% of the total mass of the aqueous phase; The oil phase solution described in S13 has an oil-to-water ratio of 1:3 with the aqueous phase solution. The shear emulsification described in S13 has the following parameters: 5000-10000 rpm, duration 10-20 min; The stirring described in S13 has the following parameters: temperature 35-45℃, speed 200-400rpm, and duration 4-8h. The centrifugal separation described in S13 has the following parameter settings: rotation speed 8000~10000rpm, duration 10~15min.

7. The method for preparing a high-toughness composite material for a foldable storage box according to claim 4, characterized in that: The chitosan-acetic acid aqueous solution described in S21 contains glacial acetic acid with a volume fraction of 1% to 2% and chitosan with a mass concentration of 1 wt% to 3 wt%. The HTPB@SiO2 monolayer microcapsules described in S22 have a mass ratio of 5:1 to 10:1 with chitosan in the chitosan acetate aqueous solution. The dispersion process described in S22 has the following parameter settings: rotation speed 5000-8000 rpm, duration 5-10 min; The spray drying described in S22 has the following parameter settings: inlet air temperature 140~160℃, outlet air temperature 70~90℃, and rotation speed 20000~30000rpm.

8. The method for preparing a high-toughness composite material for a foldable storage box according to claim 4, characterized in that: The melt extrusion described in S3 has the following parameter settings: feeding zone temperature 180-190℃, melting zone temperature 190-200℃, mixing zone temperature 200-210℃, homogenization zone temperature 200-210℃, die head temperature 210-220℃, and screw speed 300rpm.

Citation Information

Patent Citations

  • Multilayer composite polypropylene color master batch and preparation method thereof

    CN121362406A

  • Nano-microporous composite aerogel material and preparation process thereof

    CN120137333A

  • Mining composite protection long-life cable and preparation method thereof

    CN120748822A